The situation of use of environmentally friendly products of residents in urban area in Hanoi - Vũ, Thị Hồng Tứ; Lại, Vũ Kiều Trang (Trường Đại học Khoa học Xã hội và Nhân văn, 2023)
This study contributes to understanding which types of environmentally friendly products are being used commonly and the level of use of these products by people living in urban areas in Hanoi city.